Multi-walled carbon nanotube-reinforced hydroxyapatite layers on Ti6Al4V medical implants by electrophoretic deposition (EPD) - Kaya, Cengiz; Singh, Inderjeet; Boccaccini, Aldo R. (Advanced Engineering Materials, 2008)
Metallic implants such as Ti6Al4V are coated with bio-active materials such as multi-walled carbon nanotube (MWCNT)-reinforced hydroxyapatite (HA) layers by electrophoretic deposition (EPD), for encouraging the in-growth of natural bone into the prosthetic device. The deposition mass and thickness can be controlled by altering the particle concentration of the suspension, the applied field, and the deposition time. Monolithic HA and MWCNTs containing HA layers are not found to show surface microcracking after drying and sintering. The bond strength between HA coatings and the metallic substrate is significantly increased by the addition of MWCNTs. Microstructural observations indicate that MWCNTs within the sintered HA layer prevent peeling of the coating layers by acting as reinforcement network and therefore a crack deflection toughening mechanism could be operational in these composites.
UnivIS-Import:2015-03-09:Pub.2008.tech.IW.LM.multiw